Qualitative Study of Parents' Perception of Infant Immunization Based on the Health Belief Model (HBM) at the South City Health Center - Ulfaidah Usman; Siti Rahma; Mihrawaty S. Antu (Universitas Muhammadiyah Palu, 2026)
he low coverage of complete basic immunization is still a public health problem in the work area of the South City Health Center. One of the factors that contribute to this condition is the perception of parents towards immunization. Wrong or unformed perceptions can influence parents' decisions in immunizing their babies. This study aims to explore in depth the perception of parents towards infant immunization based on the Health Belief Model (HBM) component. This study uses a qualitative design with a phenomenological approach supported by the perspective of symbolic interactionism. The study was carried out in the working area of the South City Health Center by involving nine parents who had babies aged 0–18 months, who were selected by purposive sampling. Data collection was carried out through in-depth interviews, observations, and documentation. The data was analyzed thematically. The results showed that parents' perceptions varied on each component of HBM. Some parents view babies as vulnerable to disease if they are not immunized, while others feel that their babies are not at risk because they appear healthy. The perception of disease severity tends to be low because concerns about the side effects of immunization are more dominant than the perception of disease danger. Most parents understand the benefits of immunization, but there are still doubts in some participants. Psychological and social barriers, especially fear of side effects and family influence, are the most dominant factors in immunization decision-making. The conclusion of the study shows that the decision to immunize infants is influenced by the interaction of all components of HBM. Therefore, it is necessary to strengthen health education that emphasizes the benefits of immunization, reducing barriers, and increasing parental self-confidence